Environmental chemicals, breast cancer progression and drug resistance - Meriem Koual; Céline Tomkiewicz; German Cano-Sancho; Jean-Philippe Antignac; Anne-Sophie Bats; Xavier Coumoul (BMC, 2020)
Abstract Breast cancer (BC) is one of the most common causes of cancer in the world and the second leading cause of cancer deaths among women. Mortality is associated mainly with the development of metastases. Identification of the mechanisms involved in metastasis formation is, therefore, a major public health issue. Among the proposed risk factors, chemical environment and pollution are increasingly suggested to have an effect on the signaling pathways involved in metastatic tumor cells emergence and progression. The purpose of this article is to summarize current knowledge about the role of environmental chemicals in breast cancer progression, metastasis formation and resistance to chemotherapy. Through a scoping review, we highlight the effects of a wide variety of environmental toxicants, including persistent organic pollutants and endocrine disruptors, on invasion mechanisms and metastatic processes in BC. We identified the epithelial-to-mesenchymal transition and cancer-stemness (the stem cell-like phenotype in tumors), two mechanisms suspected of playing key roles in the development of metastases and linked to chemoresistance, as potential targets of contaminants. We discuss then the recently described pro-migratory and pro-invasive Ah receptor signaling pathway and conclude that his role in BC progression is still controversial. In conclusion, although several pertinent pathways for the effects of xenobiotics have been identified, the mechanisms of actions for multiple other molecules remain to be established. The integral role of xenobiotics in the exposome in BC needs to be further explored through additional relevant epidemiological studies that can be extended to molecular mechanisms.